Swiss National Foundation Sinergia Grant - Assis, Paulo de; Swiss National Foundation Sinergia Grant Bern, CH 09/06/2024 (Bern SNSF, 2023)
Evaluation Panel for Synergy Grants in Switzerland.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music